THE INCREASING OVERLAP OF JOURNALISM AND PUBLIC RELATIONS THREATS AND OPPORTUNITIES - Adriani, Roberto (PEOPLE: International Journal of Social Sciences, 2019)
Journalism is facing a new era, in which traditional rules and approaches are changing completely. The traditional distinction between journalism and Public Relations is getting more and more blurred. The purpose of this paper is to investigate why this distinction is getting blurred and what the threats and opportunities are. Through a narrative approach, the article analyses three of the main current examples of the overlap of journalism and PR: Social media Journalism, Brand Journalism and Blogging. For each one of these examples, the paper points out threats and opportunities. The main threat is that of getting click driven, feeding our audience with sensationalist news and stories. In this case journalism may abdicate its duty to be one of the pillars of public opinion. The fall out of this behavior is basically the loss of credibility. On the other hand, the main opportunity today is the possibility for journalism to get closer to its audience, bringing it more tailor-made news and stories. The take away of the article, is that this overlap between journalism and PR rises an issue about transparency.